Attention Bias and Recognition of Sexual Images - Novák, Ondřej; Bártová, Klára; Vagenknecht, Václav; Klapilová, Kateřina (Frontiers in Psychology, 2020)
Attention to sexual stimuli is necessary for the development of sexual response, yet while there is some evidence of attention bias in favor of sexual stimuli, the direction and magnitude of the effect remain unknown. A high-powered sample of 113 participants was tested using the dot-probe task (DPT) and picture recognition task (PRT) to measure visuospatial attention to erotic images. Participants showed no attention bias in the DPT (rB = 0.201, p = 0.064) but were significantly better at recognizing erotic rather than neutral or training pictures (d = 1.445 and 1.461, respectively, both p < 0.001). This indicates that spatial attention bias to sexual pictures is small, negligible, possibly even non-existent, or else the DPT is not a reliable tool to assess it. Results of the PRT, on the other hand, show that sexual stimuli are prioritized in memory and this should be explored in future research.